First record of the genus Smeryngolaphria Hermann, 1912 (Diptera: Asilidae: Laphriinae) in Peru - Sánchez Flores, Pável (2017)
The distribution of “robberflies” of the genus Smeryngolaphria Hermann, 1912 is recorded for the first time for Peru. Smeryngolaphria gorayebi Artigas, Papavero & Pimentel 1988 and Smeryngolaphria maculipennis (Macquart, 1846), two of the seven Neotropical described species, are reported from specimens deposited in the collection of the Natural History Museum at the Universidad Nacional Mayor de San Marcos (MUSM).